Coupling mechanism of double-stage ORC based on hot dry rock utilization. (December 2021) - Liu, Xueling; Niu, Jintao; Wang, Jiansheng; Zhang, Huipeng; Dong, Liwei
Abstract: For the purpose of effectively utilizing dry hot rock resource, the coupling mechanism of the double-stage Organic Rankine Cycle (ORC) power generation system is probed in present work. Six kinds of organic working fluids are employed in proposed system. By adjusting the evaporation temperature of double-stage ORC system, the thermal performance parameters of double-stage ORC system with different organic working fluids are obtained. It's found that the coupling of evaporation temperatures in double-stage ORC system affects the thermal performance parameters of the system. The Analytic Hierarchy Process (AHP) and entropy value methods are employed in optimization of present system. Compared with single-stage ORC system, double-stage ORC system can increase net output power by 8.44% to 12.20%, and the mass flow rate of organic working fluid in double-stage ORC system is greater. In addition, the thermal efficiency of double-stage ORC system reduces by 0.81% at most. Double-stage ORC can effectively reduce the temperature of heat source at the evaporator outlet, which can improve the ability of extracting heat from dry hot rock. According to the optimized results, R601 is suitable for double-stage ORC system and R600 is suitable for single-stage ORC system.